THE COMPARISON OF RECALL RIGHT OR AN INTER-TIME IMPEACHMENT MECHANISM BETWEEN AMERICAN AND INDONESIAN LAW SYSTEMS - Ibnu Elmi Achmad Slamat Pelu (UNISSULA, 2022)
This is a study of legal thought regarding regulation of the use of recall right or inter-time impeachment as political parties’ authority accommodated in MD3 Law. This recall authority has indirectly harmed the spirit of people’s sovereignty as the embodiment of a democratic state. To study, it was conducted by applying normative research methods (doctrinal research), and other regulations of written legal materials. Furthermore, it was based on three stages in conducting comparative construction, namely: (1) the descriptive phase, (2) the identification phase and (3) the explanatory phase. Based on the results through library research, the researchers found similarities between recall rights accommodated by Indonesia comparing to the implementation in the United States of America. Additionally, this similarity of recall right regulatory system concept can be used as a thought basis for legal constructions based on the actual legal protection of people’s sovereignty in Indonesian laws.